Evaluation and analysis of large-scale wireless sensor networks : a hop-distance statistic perspective - Ma, Di (2011)
In large-scale WSNs (wireless sensor networks), a source node sends its packets via multi-hop relays to a distant sink node if the source can not communicate with the sink directly. The hop-count of a sink with respect to a source is defined as the number of multi-hop relays required to transport a packet from the source to the sink. In this thesis, various statistical relationships between hop-count and source-to-sink distance are termed as hop-distance statistics. Evaluation of hop-distance statistics is an important WSN research problem. Its result can be applied to address many other WSN research issues such as range-free localization, network protocol design and evaluation, coverage and connectivity evaluation, transmission power control and many other problems.